Differential response of clones of eucalypt to glyphosate - Carvalho, Leonardo Bianco de (2015)
Weed control is commonly performed by the inter-row mechanical weeding associated to intrarow glyphosate directed spraying, causing a risk for drift or accidental herbicide application, that can affect the crop of interest. The objective was to evaluate the response of clones C219, GG100, I144, and I224 of eucalypt (Eucalyptus grandis x E. urophylla) to glyphosate doses of 0, 18, 36, 72, 180, 360, and 720 g of acid equivalent per hectare. The clones showed different growth patterns with regard to height, leaf number, stem dry weight, relative growth rate, net assimilation rate, and relative leaf growth rate. The clones I144 and GG100 were more susceptible to glyphosate, showing the doses required to reduce dry weight by 50% of 113.4 and 119.6 g acid equivalent per hectare, respectively. The clones C219 and I224 were less susceptible to glyphosate, showing the doses required to reduce dry weight by 50% of 237.5 and 313.5 g acid equivalent per hectare, respectively. Eucalyptus clones respond differently to glyphosate exposure, so that among I224, C219, GG100, and I144, the susceptibility to the herbicide is increasing.